Pear Fruits Ripening Response to Ethylene and Temperature Treatments - Tahir, Ikbal MuhammedGharib (Kurdistan Journal of Applied Research, 2021)
A factorial experiment with complete randomized design carried out in Erbil governorate, Iraq on two varieties of pears (Pyrus communis L.) spadona and compote cv. to investigate the effects of ethylene and temperature treatments on fruits ripening. The experiment includes four treatments; the control (cold storage at 0±1 C° and 85-90 relative humidity), the second was putting the fruits in ambient temperature with exposure to ethylene gas (300 mg/l) for 24 hours, third and fourth treatments were putting the fruits in the ripening cabinet at 20 C° either for 8 days, or 12 days. Results indicate that compote variety was differing significantly in decreasing weight loss and fruits firmness and increasing fruits peel pigments content and peroxidase enzyme activity compared to spadona variety. Slower ripening process was gained from cold storage treatment where the fruits remain non-ripened compared to other treatments, whereas ripening fruits at 20C° for 12 days fastened the ripening process by giving highest TSS, and lowest fruits firmness, in addition to percent of weight loss. For the condition of northern Iraq, the best treatment for ripening pear fruits is treating with ethylene gas or ripening the fruits at 20C° for 8 days.